Trajectories of Smoking Among Emerging Adult Backpackers and Their Antecedents. Issue 4 (August 2021) - Melamed, Osnat C.; Walsh, Sophie D.; Ziv, Ido; Shulman, Shmuel
Public health reports document an increase in rates of smoking among emerging adults. This study examines environmental influences and temperament as predictors of this increase. One hundred ninety-nine emerging adults were followed from before embarking on a journey outside of Israel and on their return. Participants reported their levels of daily smoking (before, during, and after the journey), novelty seeking, harm avoidance, depressive symptoms, and sociodemographics. Overall, an increase in smoking levels was observed during the backpacking experience. Latent profile analysis showed three separate trajectories of smoking: stable low (70% of participants), experimental increasing (22%), and stable high (8%). In comparison with the stable low group, the experimental increasing group was characterized by higher levels of novelty seeking, while the stable high group was characterized by higher levels of depressive symptoms. Findings highlight the interplay between smoking, temperament, and a permissive environment to explain emerging adult smoking trajectories.